Live and let die at TEMRA - Rieux-Laucat, Frédéric (American Society of Hematology, 2014)
In this issue of Blood, Rensing-Ehl and colleagues(1) provide phenotypic and genomic data revealing a FAS-dependent, stage-specific developmental checkpoint in humans presenting with autoimmune lymphoproliferative syndrome (ALPS).